Optimization The Performance of a Synchronization Controller For a 3-Phase Photovoltaic Grid-Connected System - Bennis Ghita; Karim Mohammed; Lagrioui Ahmed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
In a distributed generation system, divers renewable agents are connected to the low voltage 3 phase utility grid by an inverter which is used as power condition and must assurance the higher efficiency of the renewable agent. To achieve this level of efficiency, a unitary power factor between the utility grid voltages and the inverter currents is necessary, and a synchronization algorithm is required for the perfect synchronization between the 3-phase utility grid and the renewable agent. The aim of this paper is to present the optimization of the performance of a Synchronization controller for a 3-phase photovoltaic grid-connected system, assessing its accuracy under different conditions and studying their drawbacks and advantages. A grid connected photovoltaic system with a nominal power of 5 kW is used so as to assess the behavior of the synchronization algorithm when the 3 phase utility grid is affected by some disturbances such as voltage unbalances.